HAK PREROGRATIF KETUA UMUM PARTAI POLITIK DALAM MENCALONKAN PRESIDEN DAN WAKIL PRESIDEN - Wake, Fransiskus; Suandika, I Nyoman; Sukardi, Ni Made Rai (Jurnal Aktual Justice, 2024)
A political party is defined as an organization or association founded by an individual or group of individuals who seeks to place its members in government office for the purpose of carrying out desired political policies or programs. One thing that differentiates them from other associations is the matter of conveying a substantive interest in public affairs as part of their efforts to secure the election or election of their own representatives to public office through government policy. The right to nominate Pair Candidates for President and Vice President is the exclusive right of the parties participating in the election and is not permitted or there is no possibility at all for individual or independent Pair Candidates for President and Vice President other than those proposed by the political party or combination of political parties, and those proposed by non-party organizations. Normative Legal Research is a legal method or research carried out by examining existing library materials, more aimed at the Legislation and Laws approach by examining all laws and regulations that are properly related to the legal issue being handled to obtain objective law. (Legal Norms), regarding the Prerogative Rights of the General Chair of a Political Party in nominating the President and Vice President Conclusion Political Parties are national organizations and are formed by a group of Indonesian citizens voluntarily on the basis of the same will and ideals to fight for and defend the political interests of members , society, nation and state, as well as maintaining the integrity of the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution of the Republic of Indonesia